Bone tissue engineering in the greater omentum is enhanced by a periosteal transplant in a miniature pig model. (15th February 2019) - Naujokat, Hendrik; Lipp, Maximilian; Açil, Yahya; Wieker, Henning; Birkenfeld, Falk; Sengebusch, Andre; Böhrnsen, Florian; Wiltfang, Jörg
Aim: Reconstruction of bone defects with autologous grafts has certain disadvantages. The aim of this study is to introduce a new type of living bioreactor for engineering of bone flaps and to evaluate the effect of different barrier membranes.Materials & methods: Scaffolds loaded with bone morphogenetic proteins and bone marrow aspirate wrapped with either a collagen membrane or a periosteal flap were implanted in the greater omentum of miniature pigs.Results: Both histological and radiographic evaluation showed proven bone formation and increased density after 8 and 16 weeks, with an enhanced effect of the periosteal transplant.Conclusion: The greater omentum is a suitable bioreactor for bone tissue engineering. Endocultivation is both an innovative and promising approach in regenerative medicine. The principle of endocultivation is the translation of tissue engineering techniques to the living organism to both stimulate and guide its regenerative capacity. An individual's own body as a bioreactor promotes tissue regeneration. Bone mineral blocks are loaded with growth factors and precursor cells and wrapped with barrier membranes. Scaffolds are implanted in the greater omentum where both bone formation and vascularization occur.